Population Pharmacokinetics of Dalbavancin and Dosing Consideration for Optimal Treatment of Adult Patients with Staphylococcal Osteoarticular Infections - Cojutti, Pier Giorgio (Antimicrob Agents Chemother, 2021)
Dalbavancin is gaining interest in the treatment of complex osteoarticular (OA) infections. We aimed to conduct a population pharmacokinetic analysis of dalbavancin in a prospective cohort of adult patients with OA infections caused by Gram-positive organisms and to identify optimal dosing regimens for long-term treatment. Nonlinear mixed-effects modeling was performed with Monolix. Monte Carlo simulations were performed with six dalbavancin regimens (1,500 mg at day 1; 1,000 mg at day 1 plus 500 mg at day 8; 1,500 mg at days 1 and 8; and 1,500 mg at days 1 and 8 plus 500, 1,000, or 1,500 mg at day 36) to assess the probability of target attainment (PTA) of three pharmacodynamic targets of area under the concentration-time curve for the free, unbound fraction of a drug at 24 h/MIC (fAUC(24h)/MIC) against Staphylococcus aureus (>27.1, 53.3, and 111.1). The cumulative fraction of response (CFR) was calculated against the MIC distribution of both methicillin-resistant S. aureus (MRSA) and methicillin-susceptible S. aureus (MSSA). Desirable PTAs and CFRs were ≥90%. Fifteen patients provided 120 plasma concentrations. Most (73.3%) had prosthetic joint infections. The clinical cure rate was 87%. A two-compartment model with linear elimination well described the data. No covariate was retained in the final model. Pharmacokinetic dalbavancin estimates were 0.106 liter/h for total body clearance (CL) and 36.4 liter for volume of distribution at steady state(V(ss)). The tested dosing regimens granted desirable CFRs against S. aureus at the most effective pharmacokinetic/pharmacodynamic (PK/PD) target for a period ranging 3 to 9 weeks. Giving a regimen of two 1,500-mg doses of dalbavancin 1 week apart may ensure efficacy against both MSSA and MRSA up to 5 weeks in patients with OA infections. Clinical assessment at that time may allow for considering whether an additional dose should be administered for prolonging effective treatment.